Aplikasi Pemanfaatan Maggot (Larva) Sebagai Pengurai Sampah Rumah Tangga - Rahmat Ramadansur; Marta Dinata; Rikizaputra Rikizaputra (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity is based on the problems and needs of residents to process several types of waste/organic waste that is often found wasted. To find alternative solutions to the problems above, training was held and made media for maggot decomposition in the form of a container for residents of RW 06, Padang Terubuk Village. With the aim of training the residents of RW 06 to make media for the decomposition of household waste using maggots (larvae) that can minimize organic waste. The methods used to achieve the objectives are: 1) Pretest: in the form of a questionnaire given before the counseling and training activities (submission of material and discussion) begin, 2) Submission of material: in the form of delivering media material where household waste is decomposed using maggot (larvae) that can minimize organic waste, 3) Direct practice of making media for household waste decomposition using maggot (larvae), 4) household waste decomposition using maggot (Larvae, 5) Posttest: in the form of a questionnaire given after the counseling and training activities are completed. From the results and discussions that have been described previously, it can be concluded that this service activity provides positive results because this activity can help difficulties and meet the needs of participants in decomposing household waste.